POST-MASTECTOMY SURGICAL SITE INFECTION RATES IN FEMALES WITH BREAST CARCINOMA IN PREMENOPAUSAL AGE: A SINGLE CENTER STUDY - IMRAN , M; ANWAR, MI; JAMEEL, MA; NAEEM , HM (Biological and Clinical Sciences Research Journal, 2024)
Breast surgery, like mastectomy, is generally considered a low-risk procedure for surgical site infections (SSIs), but when SSIs do occur, they can lead to significant complications. Identifying risk factors to improve patient outcomes and minimize complications is essential. Objective: This study aimed to determine the frequency of post-mastectomy surgical site infections (SSI) in premenopausal females with breast carcinoma and to identify the associated risk factors. Methods: This descriptive case study included 100 premenopausal females diagnosed with breast carcinoma who underwent mastectomy at a tertiary care hospital, Shaikh Zayed Hospital Lahore, from April 2024 to August 2024. The age range of participants was 25-45 years, with a mean age of 39 ± 5.3 years. Demographic data, including age, gender, body mass index (BMI), comorbidities, and American Society of Anesthesiologists (ASA) score, were collected. Intraoperative variables such as blood loss (mean: 350 ± 50 ml) and surgery duration (mean: 120 ± 15 minutes) were also recorded. All patients received standard postoperative antibiotic prophylaxis, including cefazolin or clindamycin, for those allergic to penicillin. The surgical site was assessed 30 days postoperatively for signs of infection, including erythema, pus discharge, or fever exceeding 38°C. SSIs were categorized based on the Centers for Disease Control and Prevention (CDC) guidelines into superficial, deep, and organ/space infections. Results: The overall infection rate was 7.5% (n=7). Of these, 4 cases were superficial infections, while 3 involved deeper tissue layers, requiring drainage and further antibiotics. Factors significantly associated with an increased risk of disease in the multivariate logistic regression model included a high wound class (contaminated or dirty; OR: 3.2, p=0.01), elevated ASA score (ASA III-IV; OR: 2.8, p=0.03), high BMI >30 (OR: 3.5, p=0.002), diabetes (OR: 4.1, p=0.001), use of surgical drains (OR: 2.9, p=0.02), and reoperation (OR: 4.3, p=0.005). The mean hospital stay was extended by 4.5 days (from 5.2 ± 1.5 days in non-infected patients to 9.7 ± 3.1 days in infected cases). Conclusion: The study found a post-mastectomy surgical site infection rate of 7.5% in premenopausal females, with significant risk factors including high BMI, diabetes, use of surgical drains, and the need for reoperation. A high wound class and elevated ASA score also predicted increased infection risk. Addressing these modifiable risk factors through optimized perioperative care, such as better glycemic control, judicious use of surgical drains, and minimizing reoperations, may help reduce SSI rates and improve outcomes for breast cancer patients.